Швидкість збіжності до ергодичного розподілу довжини черги в системах типу Mθ/G/1/N - Братійчук, А.М. (Український математичний журнал, 2007)
Для систем обслуживания типа M θ/G/1 с ограниченной очередью найдены удобные формулы для эргодического распределения длины очереди, получена оценка скорости сходимости распределения длины очереди в переходном режиме к эргодическому, а также приведены вычислительные алгоритмы для нахождения скорости сходимости. For finite capacity queueing systems of the type M θ/G/1, the convenient formulas for the ergodic distribution of a queue length are obtained. An estimate of a rate of convergence of the distribution of queue length in the trasient regime to the ergodic distribution is obtained and computational algorithms for finding the convergence rate are presented.